2017
DOI: 10.1128/jvi.02438-16
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-Dependent LMP1 Expression Is Required for Efficient Lytic Epstein-Barr Virus Reactivation in Epithelial Cells

Abstract: Epstein-Barr virus (EBV)-associated diseases of epithelial cells, including tumors that have latent infection, such as nasopharyngeal carcinoma (NPC), and oral hairy leukoplakia (OHL) lesions that have lytic infection, frequently express the viral latent membrane protein 1 (LMP1). In lytically infected cells, LMP1 expression is activated by the BRLF1 (R) immediate early (IE) protein. However, the mechanisms by which LMP1 expression is normally regulated in epithelial cells remain poorly understood, and its pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
67
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 85 publications
7
67
0
1
Order By: Relevance
“…Prior to rafting, oral epithelial cells can be maintained in vitro as monolayers in their undifferentiated state by subconfluent culture in serum-free medium. As monolayers, they can be differentiated either through treatment with fetal bovine serum (FBS) and calcium or by the addition of methylcellulose to the growth medium (25,36,37). Our NOKs and hGETs maintained as monolayers in serum-free media did not express involucrin, but involucrin expression (differentiation) could be induced either by FBS and calcium or by methylcellulose ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Prior to rafting, oral epithelial cells can be maintained in vitro as monolayers in their undifferentiated state by subconfluent culture in serum-free medium. As monolayers, they can be differentiated either through treatment with fetal bovine serum (FBS) and calcium or by the addition of methylcellulose to the growth medium (25,36,37). Our NOKs and hGETs maintained as monolayers in serum-free media did not express involucrin, but involucrin expression (differentiation) could be induced either by FBS and calcium or by methylcellulose ( Fig.…”
Section: Resultsmentioning
confidence: 89%
“…The latent form of infection allows the virus to persist for the lifetime of the host, whereas the lytic form of infection enables infectious virion production and transmission from cell to cell and from host to host. Both forms of infection are essential for the long-term success of the virus (45). It is also speculated that once EBV is reactivated into the lytic cycle, the induced expression of LMP1 is considered to be critical for efficient virus release and infection of new host cells.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that LMP1 serves an important role in the EBV lytic cycle (24,45,46). While LMP1 may be expressed in some states of EBV latency, significant induction of full-length LMP1 is frequently observed during virus reactivation into the lytic cycle (13,47,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The granular epithelial layer contains apoptotic cells, and the stratum corneum is characterized by keratin cells of fibrils which form an extracellular barrier. 14 After lytic replication in epithelial cells, the virus spreads to all lymphoid tissues and infects naive B cells through binding of glycoprotein gp350 virus to the CD21 receptor on the B cell's surface. The infected B cells trigger specific primary cytotoxic cell responses that ultimately control EBV infection.…”
Section: Introductionmentioning
confidence: 99%